The Role of Parents’ Marital Relationship Quality in Adolescents’ Self-Esteem with the Mediating Role of Attachment Style: A Structural Modeling Approach - Mohammadi, Fateme; Sohrabi, Nadereh; Kouroshnia, Maryam; Zarnaghash, Maryam (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: This study aimed to examine whether parents’ marital relationship quality predicts adolescents’ self-esteem directly and indirectly through the mediating role of attachment style using a structural equation modeling approach. Methods and Materials: The study employed an applied, descriptive–correlational design using path analysis. The statistical population consisted of adolescents aged 14–18 years and their parents residing in Sepidan County in 2025. A multistage cluster sampling method was used to select the sample from upper secondary schools, resulting in the participation of 187 adolescents and 183 parents. Data were collected using standardized instruments, including the Rosenberg Self-Esteem Scale, the Revised Dyadic Adjustment Scale for marital relationship quality, and the Hazan and Shaver Attachment Styles Scale. After obtaining informed consent, questionnaires were administered in person. Data analysis was conducted using SPSS (version 23) for preliminary analyses and AMOS (version 23) for testing the structural model and evaluating model fit indices. Findings: Structural equation modeling revealed that parents’ marital relationship quality had a significant direct effect on adolescents’ self-esteem (β = 0.451, p < .001). Attachment style also showed a significant direct effect on adolescents’ self-esteem (β = 0.387, p < .001). In addition, marital relationship quality significantly predicted adolescents’ attachment style (β = 0.381, p < .001). Mediation analysis indicated that attachment style partially mediated the relationship between marital relationship quality and adolescents’ self-esteem, as the direct path remained significant after inclusion of the mediator, while its magnitude decreased. Overall model fit indices demonstrated an acceptable fit between the proposed model and the empirical data. Conclusion: The findings indicate that parents’ marital relationship quality plays a crucial role in adolescents’ self-esteem both directly and indirectly by shaping adolescents’ attachment styles.